Evaluating Accessible Tourism: A Descriptive And Correlation Analysis Of Tourist Accessibility Requirements And Perceptions (International Journal of Environmental Sciences, 2025)
Accessible tourism is an emerging area of interest within the tourism industry, aiming to make destinations, services, and experiences available to all travellers, including those with disabilities or mobility limitations. Purpose: This study investigates the current landscape of accessible tourism, analysing satisfactory levels, awareness and the demand for accessible facilities amongst the travellers. Design/Methodology/Approach: Using a structured questionnaire, data were gathered from 330 respondents, encompassing individuals with and without accessibility needs. Descriptive statistics is conducted using SPSS to determine the impact of accessibility features, such as transportation, accommodations, attractions and the traveller’s satisfaction. Findings: The findings reveal a significant positive correlation between the availability of accessible facilities and overall satisfaction. Additionally, the results demonstrate that awareness of accessible tourism is directly linked to a preference for destinations offering inclusive services, underscoring the role of education in fostering demand. Results: Accessibility in accommodations and public spaces show moderate satisfaction levels whereas customer service was highlighted as an area requiring improvement, particularly in terms of staff training and awareness. The research identifies specific gaps in infrastructure, information accessibility and staff preparedness that hinder the efficiency and development of accessible tourism, thereby offering actionable insights for policymakers and tourism operators. Originality/Value: Accessible tourism with novelty, addresses social inclusion and presents a broader perspective of economic opportunity through expansion of potential market for tourism services. The findings elaborate in depth understanding of accessible tourism and sketch future research foundation to improve tourism experiences for travellers with diverse needs.